The Hungry Stomach: Physiology, Disease, and Drug Development Opportunities - Sanger, Gareth J.; Hellström, Per M.; Näslund, Erik (Frontiers in Pharmacology, 2011)
During hunger, a series of high-amplitude contractions of the stomach and small intestine (phase III), which form part of a cycle of quiescence and contractions (known as the migrating motor complex, MMC), play a “housekeeping” role prior to the next meal, and may contribute toward the development of hunger. Several gastrointestinal (GI) hormones are associated with phase III MMC activity, but currently the most prominent is motilin, thought to at least partly mediate phase III contractions of the gastric MMC. Additional GI endocrine and neuronal systems play even more powerful roles in the development of hunger. In particular, the ghrelin-precursor gene is proving to have a complex physiology, giving rise to three different products: ghrelin itself, which is formed from a post-translational modification of des-acyl-ghrelin, and obestatin. The receptors acted on by des-acyl-ghrelin and by obestatin are currently unknown but both these peptides seem able to exert actions which oppose that of ghrelin, either indirectly or directly. An increased understanding of the actions of these peptides is helping to unravel a number of different eating disorders and providing opportunities for the discovery of new drugs to regulate dysfunctional gastric behaviors and appetite. To date, ghrelin and motilin receptor agonists and antagonists have been described. The most advanced are compounds which activate the ghrelin and motilin receptors which are being progressed for disorders associated with gastric hypomotility.